2018
DOI: 10.1007/jhep01(2018)139
|View full text |Cite
|
Sign up to set email alerts
|

Tensor network and (p-adic) AdS/CFT

Abstract: Abstract:We use the tensor network living on the Bruhat-Tits tree to give a concrete realization of the recently proposed p-adic AdS/CFT correspondence (a holographic duality based on the p-adic number field Q p ). Instead of assuming the p-adic AdS/CFT correspondence, we show how important features of AdS/CFT such as the bulk operator reconstruction and the holographic computation of boundary correlators are automatically implemented in this tensor network.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 67 publications
(136 reference statements)
7
62
0
Order By: Relevance
“…Recent reviews of the BT tree can be found in [1,9,10], so here we limit ourselves to those features most relevant to the current discussion.…”
Section: Bruhat-tits Treementioning
confidence: 99%
See 3 more Smart Citations
“…Recent reviews of the BT tree can be found in [1,9,10], so here we limit ourselves to those features most relevant to the current discussion.…”
Section: Bruhat-tits Treementioning
confidence: 99%
“…In our previous study relating tensor networks to p-adic AdS/CFT [1], the tensor network plays the role of a "wavefunction" for the p-adic CFT. To compute correlation functions, one glues a tree tensor network with its conjugate along the common boundary, which is the analogue of the Poincaré cutoff surface in the BT tree (see Fig.…”
Section: The Wavefunction Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…The tensor network states approximates the CFT state at the boundary, while the structure of tensor network emerges an bulk dimension built by layers of tensors. Tensors in the tensor network correspond to local degrees of freedom in the bulk [31][32][33]. The architecture of the TN may be viewed as a process of real-space renormalization, such as multiscale entanglement renormalization ansatz (MERA), where the renormalization scale relates to the coordinate of the emergent dimension [2,7,34,35].…”
Section: Jhep11(2017)148mentioning
confidence: 99%